The Characteristics of the Sundanese Language ''Aing Tangerang'': Diversity and Loss of Cultural Identity - Ijum Setiawan (International Research and Development for Human Beings (IRDH), 2025)
In recent decades, a worrying phenomenon has occurred is the declining using of the Sundanese language among the younger generation. This research focussed on various social, cultural, and psychological aspects that affect the use of Sundanese in Tangerang, with the aim of providing insights that can help communities, governments, and educational institutions in formulating more effective conservation strategies. This study used a qualitative approach with in-depth interview methods and participatory observation. The results showed that the use of Sundanese in Tangerang continues to live in certain families and communities, although not as much as in the past. People in Tangerang still maintain this language in their daily conversations, although it is starting to be rarely found in public spaces. One of the characteristics of the Sundanese language that still survives in Tangerang is the expression